Attitude of Secondary School Students’ towards Mental Illness in Relation to Location (Rural and Urban) in Plateau State, Nigeria - Da’am , Emmanuel Haniya; Kyamru , James Illya; E. S. Samuel , E. S. Samuel (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The purpose of the study was to determine the attitude of secondary school students’ attitudes towards mental illness in relation to location (rural and urban) in Plateau State, Nigeria. Three research questions were posed with corresponding null hypotheses postulated to guide the study and tested at .05 level of significance. Descriptive research design was used for the study. The population for the study consisted of all secondary schools students in Plateau State, which was one million five hundred and eighteen thousand, eight hundred and ninety (1,518,890). The sample size for the study was 3,456 secondary school students. The instrument used for data collection was questionnaire. The research questions were answered using descriptive statistic of mean while the null hypotheses was tested at .05 level of significance using t-test statistic. The major findings of the study were as follows: the students’ attitudes towards mental illness (x=2.76), causes of mental illness (x=2.76), coping strategies for mental illness (x=2.74) and prevention of mental illness was positive. Rural and urban students had positive attitude towards all the dimensions of mental illness. There was no significant difference in attitude of students of rural and urban regarding all the dimensions of mental illness. On the basis of the findings and conclusion, recommendations were made. Among them are: Ministries of Education, Health, Youth, Sports and Culture should mount seminars and workshops on mental and emotional health towards empowering the students to have more positive attitudes towards mental illness and the National Health Science Curriculum should be given full implementation in all the secondary schools in the State.